2006
DOI: 10.1097/01.shk.0000194041.18699.6f
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Inhibits Lipopolysaccharide-Induced Cytoplasmic Phospholipase A2 Activation and Protects Against Endotoxin Shock in Mouse

Abstract: Glutamine (Gln) supplementation is known to play a beneficial role in a number of settings of critical illness as well as laboratory models of endotoxin shock. We have investigated a molecular mechanism of the protective role of Gln in lipopolysaccharide (LPS)-induced shock using a mouse model. To examine the effectiveness of Gln, Gln was administered before or after LPS injection. Treatment of Gln before, but not after, LPS injection resulted in inhibition of nuclear factor kappaB activation and tumor necrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 30 publications
3
25
0
Order By: Relevance
“…Gln was dissolved in Hartmann's solution (30 mg/ml), and 750 mg/kg of Gln was i.p. administered as described previously (14). Quercetin from Sigma-Aldrich (400 mg/kg) was administered i.p.…”
Section: Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gln was dissolved in Hartmann's solution (30 mg/ml), and 750 mg/kg of Gln was i.p. administered as described previously (14). Quercetin from Sigma-Aldrich (400 mg/kg) was administered i.p.…”
Section: Reagentsmentioning
confidence: 99%
“…The protective effects of PLA 2 inhibitors in endotoxic shock (10,11), or reduced septic symptoms in PLA 2 -deficient mice (12,13), indicate that PLA 2 is an essential component in the pathogenesis of endotoxic shock. We have previously shown that Gln protects animals from endotoxic shock through its inhibition of cPLA 2 activity (14), and this activity of Gln was also associated with suppression of asthma in mice (15).…”
mentioning
confidence: 99%
“…Both MKP-1 induction and MKP-1 mediated p38 dephosphorylation within 5 min following Gln administration, suggesting that Gln dephosphorylated cPLA 2 indirectly through MKP-1-mediated p38 dephosphorylation. However, Gln dephosphorylated p-cPLA 2 rapidly within 5 min, as in the case of p38 in LPS-injected mice [13,14,20], suggesting that phosphatase is involved. Gln injection resulted in a rapid induction of MKP-1 within 5 min, which coincided with Gln-induced dephosphorylation of cPLA 2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Gln was dissolved in sterilized distilled water to 3%. A volume of 0Á5 ml (750 mg/ kg) [12][13][14][15] was administered intraperitoneally (i.p.) 10 min before or 10 min after LPS injection.…”
Section: Reagentsmentioning
confidence: 99%
See 1 more Smart Citation